PENGARUH SALES GROWTH, AUDIT COMMITTEE, KOMISARIS INDEPENDEN DAN LEVERAGE TERHADAP NILAI PERUSAHAAN - Vincentius Harisanto; Widyasari Widyasari (Jurnal Paradigma Akuntansi, 2023)
This research aims at how the effect of sales growth and leverage toward firm value, and the role of the audit committee and independent commissioner on firm value in trading and service companies listed on the Indonesia stock exchange during 2017-2019. The sample was selected by purposive sampling method and valid data were 29 companies from 154 companies. Data Processing techniques use the Eviews 11 (Econometric Views) for Windows and Microsoft Excel 2019 program. The results of this research indicate that sales growth and leverage have a positive and insignificant effect toward firm value, while the audit committee and independent commissioners have a negative and insignificant effect on firm value. The implication of this research is the need for for other factors to support else sales growth and leverage to influence firm value and the need for an increased the role of audit committee and independent commissioners to increase firm value which will provide a good signal for investors.